국내신약개발에 영향을 미치는 요인 및 개선방안 연구 : 국내 제약회사중 상위매출 41개 회사의 특성을 중심으로 - 홍연탁 (연세대학교 보건대학원, 1987)
[한글] 우리나라에서의 신약개발은 신물질 창조는 이루지 못하고 외국에서 기히 개발된 신제품을 도입하는 수준이다. 외자의 개방시책과 물질특허제도 도입이 현실화 됨에 따라 해외의존도를 탈피하고 국제 경쟁력 재고를 위한 연구 개발이 더욱 요청되고 있다. 이에 신약개발에 영향을 주는 요인과 개선방안응 연구하기 위하여 1986년 매출액의 상위 50개 제약기업을 대상으로 하여 설문에 응답한 41개 제약회사의 특성과 신약개발에 영향을 주는 요인을 다변수 회귀분석 방법으로 분석하였으며 개방설문은 유사하다고 판단되는 그룹을 분류정리하여 전산조직을 활용하여 분석하였고 외국의 신약제도에 관한 관계문헌을 수집조사하여 다음과 같은 결과를 얻었다. 1. 우리나라에서 신물질 창조는 이루워지지 못하고 외국에서 기 개발된 신제품을 도입하는 수준이며, 제약회사의 특성은 영향을 주는 요인이 되지 못하였다. 2. 개방설문을 통하여 수집된 자료에서 신약허가 제도의 개선방안등을 분석한 결과 제도상 다음과 같은 몇가지 주요 문제점을 갖고 있었다. 첫째 우수실험동물 확보를 위한 관리기준 보완 둘째 약제의 특성에 따라 전임상시험 일부 면제와 임상시험 예수조정 셋째 부작용 관계 전문부서 설립 홍보등 과학적 체계적 운영 3. 외국의 신약허가제도의 관계문헌을 조사하여 우리나라 허가제도에서 개선할 사항을 전문가의 자문을 받은 결과 다음과 같은 개선점이 지적 되었다. 첫째 보사부 약정국에 안전과를 신설하여 안전성 및 유효성을 전문적으로 관장하여야 한다. 둘째 신약허가에 있어 일반용의약품과 치료용의약품으로 구분하고 중앙약사 심의위원회의 약효별 전문가로 신약소분위를 구성 자문을 받도록하고 시판후 감시제도(PMS)를 도입한다. The Study On Factors Affecting the New Drug Development and Improvement Scheme Hong, Youn Tack Graduate School of Health Science and Management, Yonsei University (Directed by Professor Yu, Seung Hum, M.D.) The level of new drug development in Korea is situsted at the stage of intriducing new drugs developed in foreign countrise rather than creating new substances. According to liberalization policy og foreign capital introduction and actualization of product patent system, research & development of new drug is requested increasingly in order to break away from the foreign dependence and to raise international competitive power. For the study of factors affecting the new drug development and improvement scheme, the characteristic and factors affecting the new drug development of the 50 high-ranking pharmaceutical companies in 1986, were analyzed from open questionnaires of these companies classified and arranged into similar groups. Analysis was made using multiple regression analysis by computer New drug approval systems inthe foreign countries were surveyed through documents of the related countries. 1. Characteristics of the pharmaceutical companies were not the new drug development in Korea is situated at the stage of introducing new drugs developed in foreign countries rather than creating new substances. 2. According to analysis of improvement schemes in the new drug approval major institutional problems were pointed out. First, complement of animal care standard ensuring good quality animal for GLP. Second, partial exemption of pre-clinical studies and adjustment of patient numers in clinical studies according to characteristics of a drug. Third, establishment of professional department talking chage of adverse reactions, and systematic operation such as publicity activities, etc. 3. The proposal matters for the new drug approval system in Korea were derived. through consultation of experts, from the review of documents regarding the new drug approval systems in foreign countries. First, safety& efficacy matters should be professionally managed by the Safety Evaluation Division which will be newly organized within the Pharmaceutical Affairs Bureau, MOHSA. Second, for new drug approval, together with classified approval to a non-presciption drug or a prescription drug, consultation by the New Drug Subcommitteen composed of among the CPARC members, is required. Introduction of PMS system is also required [영문] The level of new drug development in Korea is situsted at the stage of intriducing new drugs developed in foreign countrise rather than creating new substances. According to liberalization policy og foreign capital introduction and actualization of product patent system, research & development of new drug is requested increasingly in order to break away from the foreign dependence and to raise international competitive power. For the study of factors affecting the new drug development and improvement scheme, the characteristic and factors affecting the new drug development of the 50 high-ranking pharmaceutical companies in 1986, were analyzed from open questionnaires of these companies classified and arranged into similar groups. Analysis was made using multiple regression analysis by computer New drug approval systems inthe foreign countries were surveyed through documents of the related countries. 1. Characteristics of the pharmaceutical companies were not the new drug development in Korea is situated at the stage of introducing new drugs developed in foreign countries rather than creating new substances. 2. According to analysis of improvement schemes in the new drug approval major institutional problems were pointed out. First, complement of animal care standard ensuring good quality animal for GLP. Second, partial exemption of pre-clinical studies and adjustment of patient numers in clinical studies according to characteristics of a drug. Third, establishment of professional department talking chage of adverse reactions, and systematic operation such as publicity activities, etc. 3. The proposal matters for the new drug approval system in Korea were derived. through consultation of experts, from the review of documents regarding the new drug approval systems in foreign countries. First, safety& efficacy matters should be professionally managed by the Safety Evaluation Division which will be newly organized within the Pharmaceutical Affairs Bureau, MOHSA. Second, for new drug approval, together with classified approval to a non-presciption drug or a prescription drug, consultation by the New Drug Subcommitteen composed of among the CPARC members, is required. Introduction of PMS system is also required
보건학과/석사